Biodiversity and characteristic of octocoral communities (Octocorallia: Alcyonacea and Gorgonacea) in Cu Lao Cham Marine Protected Area, Quang Nam province - Ben, Hoang Xuan; Quang, Thai Minh (Vietnam Journal of Marine Science and Technology, 2020)
The article showed the biodiversity and characteristic of Octocoral communities in Cu Lao Cham Marine Protected Area (MPA). A total of 165 samples were collected and identified as material of the Octocorals from 9 survey sites of Cu Lao Cham Marine Protected Area. The material represents 45 taxa belonging to 12 genera and seven families. Among them, Sinularia genus has the highest diversity with 19 species, Sarcophyton with 8 species and Lobophytum with 6 species. The other genera have one or two species. The diversity of Octocorals species in Cu Lao Cham Marine Protected Area is quite high after Nha Trang and Ly Son MPAs. Soft coral cover in Cu Lao Cham Marine Protected Area is the highest with average coverage 21.2% (±7.0 SE) compared with other MPAs of Vietnam. Distribution of Octocorals in Cu Lao Cham Marine Protected Area is mainly at 4–6 m (average coverage obtained 30%) and the cover decreases to the end of reef distribution. Our results showed that there are two distinguishing assemblages of Octocoral communities whose differences are the distribution characteristics, dominance of genera and species diversity